Expression of ADAM28 and IGFBP-3 Genes in Patients with Colorectal Cancer — A Preliminary Report. (January 2013) - Nowakowska-Zajdel, E.; Mazurek, U.; Wierzgoń, J.; Kokot, T.; Fatyga, E.; Ziółko, E.; Klakla, K.; Błażelonis, A.; Waniczek, D.; Głogowski, Ł.; Kozowicz, A.; Niedworok, E.; et al.
Adamalisynes ( ADAMs) play an important role in inter-membrane interactions, cell adhesion and fusion processes and protein shedding from the cell surface. Many reports indicate that members of the ADAMs family are overexpressed in human cancer. The aim of the present study was to evaluate ADAM28 and Insulin Like Growth Factor Binding Protein-3 ( IGFBP-3)) gene expression in colorectal carcinoma tissues with regard to the overweight or obese status of the patients using an oligonucleotide microarray technique. Fresh tissue specimens were obtained from colorectal cancer patients during surgical treatment. Eighteen specimens from tumour and 18 normal tissue specimens from colorectal cancer patients at clinical stages III and IV were analysed. The examined patients were divided into two groups; those with BMI≥25 and those with normal BMI. The control group consisted of 18 specimens of non-neoplastic colon tissues, which were divided between overweight/obese and normal body weight patients. The gene transcriptional activity from the specimens was analysed using an oligonucleotide microarray technique. Microarrays and rinsing and marking solutions were prepared according to the procedure in the Gene Expression Analysis Technical Manual. The following conclusions were made: i) change of ADAM28 and IGFBP-3 genes expression are present in the normal tissue in overweight/obese patients with colorectal cancer only; ii) the observed molecular variability of ADAM28 and IGFBP-3 expression may be an initial process of cancer proliferation; iii) the histopathologically normal surgical margin in this group of patients was not equal to the molecular margin.